Unveiling Niaprazine’s Potential: Behavioral Insights into a Re-Emerging Anxiolytic Agent - Hanna Trebesova; Martina Monaco; Sara Baldassari; Giorgia Ailuno; Edilio Lancellotti; Gabriele Caviglioli; Anna Maria Pittaluga; Massimo Grilli (Biomedicines)
Ongoing global research actions seek to comprehensively understand the adverse impact of stress and anxiety on the physical and mental health of both human beings and animals. Niaprazine (NIA) is a chemical compound that belongs to the class of piperazine derivatives. This compound has recently gained renewed attention due to its potential therapeutic properties for treating certain conditions such as anxiety. Despite its potential benefits, the behavioral effects of NIA have not been thoroughly investigated. This study aimed to examine NIA’s potential as an anti-anxiety and anti-stress agent. After administering either vehicle or NIA in their drinking water to mice for 14 days, we conducted behavioral analyses using the Marble Burying Test and the Elevated Plus Maze test. NIA-treated mice spend more time in the open arms and bury fewer marbles. Moreover, a stability study confirmed the linear relationship between NIA concentration and its response across concentrations encompassing the NIA mother solution and the NIA solutions administered to mice. Also, a preliminary synaptic toxicity analysis showed no direct damage to cortical nerve endings. Here, we show that NIA can modulate anxiety-related behaviors without significantly impacting exploratory activity or adverse effects. Our work describes new findings that contribute to the research on safer and more tolerable anxiety management options.